Brief Report: Sexual Risk Behaviors of HIV Seroconverters in the US Army, 2012–2014. (1st December 2015) - Hakre, Shilpa; Scoville, Stephanie L.; Pacha, Laura A.; Peel, Sheila A.; Kim, Jerome H.; Michael, Nelson L.; Cersovsky, Steven B.; Scott, Paul T.
Abstract : Abstract: The United States (US) Army implemented a comprehensive HIV characterization program in 2012 following repeal of the Don't Ask, Don't Tell policy banning openly homosexual individuals from serving in the US military. Program staff administered a standardized case report form to soldiers newly diagnosed with HIV from 2012 to 2014 in compliance with new program requirements. The case report form documented sociodemographic, sexual, and other risk behavior information elicited from US Army regulation-mandated epidemiologic interviews at initial HIV notification. A majority of HIV-infected soldiers were male and of black/African American racial origin. In the HIV risk period, male soldiers commonly reported male–male sexual contact, civilian partners, online partner-seeking, unprotected anal sex, and expressed surprise at having a positive HIV result. Don't Ask, Don't Tell repeal allows for risk screening and reduction interventions targeting a newly identifiable risk category in the US Army. At-risk populations need to be identified and assessed for possible unmet health needs.